The Superior Labial Frenulum in Newborns: What Is Normal?. (10th July 2017) - Santa Maria, Chloe; Aby, Janelle; Truong, Mai Thy; Thakur, Yogita; Rea, Sharon; Messner, Anna
Introduction and Objectives : There has been an emergence of procedures to release the superior labial frenula in infants, yet little is known about the normal appearance or incidence of severe attachment, or "lip-tie." The objective of this article was to develop a classification system for superior labial frenula and to estimate the incidence of different degrees of attachment. Methods : A prospective cross-sectional study. Newborns were examined and had photographs taken of their upper frenula. Relevant medical professionals rated the appearance of the labial frenula using a previously described Kotlow classification system. The raters assessed each photograph twice and were blinded to their previous rating and to other raters' scores. Results : All newborns have a labial frenula, with most attached at the gingival margins (83%). Raters had poor intra- and interrater reliability (64% to 74% and 8%, respectively), using the Kotlow classification system, which improved when the classification system was simplified. Conclusions : The Kotlow classification of lip-tie fails to be reproducible by relevant experts. The majority of infants had a significant level of attachment of the labial frenulum. As more procedures are done to release the upper lip frenulum, it is important to understand what degree of attachment is normal, or more common.